SELF-EFFICACY, SELF REGULATION AND GRIT ON ACADEMIC STRESS AMONG VOCATIONAL SCHOOL STUDENTS - Utami, Dewi Ayu; Sariwulan, Tuty; Adha, Maulana Amirul (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2023)
This study aims to determine the data descriptions of self-efficacy, self-regulation, grit and academic stress in office management and business services (MPLB) students at SMK Negeri 16 Jakarta. The research method used in this study is quantitative descriptive method. The population in this study was 176 students in classes X, XI and XII, Department of Office Management and Business Services (MPLB). The technique for determining the sample in this study used a stratified random sampling technique using the Issac and Michael table with an error rate of 5% so that the sample in this study was 122 students. The results of the descriptive analysis from this research found that the self-efficacy variable had the largest mean value with a score of 3.762 and the lowest value with a score of 3.516. Followed by the self-regulation variable which has the largest mean value with a score of 3.811 and the lowest score is 3.525. Furthermore, the grit variable has the largest mean value with a score of 4.066 and the lowest value with a score of 3.574 and the academic stress variable has the largest mean value with a score of 3.057 and the lowest value with a score of 2.492.